Let's be civil: Elaborating the link between civility climate and hospital performance. Issue 3 (July 2019) - Oppel, Eva-Maria; Mohr, David C.; Benzer, Justin K.
Abstract : Background: The importance of interpersonal behavior at the workplace is increasingly recognized in the health care industry and related literature. An unresolved issue in the existing health care research is how a climate of courteous interpersonal behavior may form the foundation for strong hospital care performance. Purpose: The aim of this study was to test the link between a climate of courteous interpersonal behavior, termed "civility climate, " and hospital care performance. We conceptualize a multidimensional model of care performance by contrasting two dimensions: performance as perceived by employees and performance as perceived by patients. Furthermore, for both performance perspectives, we test an intermediate variable (error orientation climate) that may explain the relationship between civility climate and hospital care performance. Methodology: The 2011 study sample comprised responses from 6, 094 nurses and 38, 627 patients at 123 Veterans Health Administration acute care inpatient hospitals in the United States. We developed and empirically tested a theoretical model using regression modeling, and we used a bootstrap method to test for mediation. Results: The results indicate a direct effect of civility climate on employee perceptions of care performance and an indirect effect mediated by error orientation climate. With regard to patient perceptions of care performance, the analyses reveal a direct effect of civility climate. The indirect effect mediated by error orientation climate was not supported. Practice Implications: Our findings point to the importance of strengthening interpersonal interactions for ensuring and improving both employees' and patients' perceptions of care, which constitute key success factors in the increasingly competitive hospital market. The insights may further stimulate discussion regarding interventions to foster a strong civility climate in hospitals.